Hepatoprotective Effects of Momordica dioica Against Acetaminophen-induced Liver Damage in Rats: An Experimental Study - Pushpalatha Tanneeru; Kalpana Ramachandran; V Gayathri; D Haripriya; Shonam Tamrakar (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Hepatotoxicity from acetaminophen is a major contributor to liver damage. Among the most popular analgesics, acetaminophen has few adverse effects when taken in therapeutic dosages; however, acetaminophen abuse frequently results in hepatotoxicity. Aim: The aim of this study is to investigate the histopathological changes induced by a therapeutic dose of N-acetyl-para-aminophenol (APAP) and to explore the hepatoprotective role of the oral co-administration of Momordica dioica fruit extract in mitigating hepatotoxicity induced by APAP in rats. Materials and Methods: The present experimental study was conducted in the central animal facility of Sri Ramachandra Institute of Higher Education and Research, Chennai, Tamil Nadu, India, between February to April 2024. Thirty-six healthy male albino Wistar rats were utilised in this study, randomised and divided into six groups (G1-G6) of six rats each. The rats were administered APAP (i.p.) and Momordica dioica (MD) orally for 42 days as follows: (G1) Control (normal saline), (G2) APAP (250 mg/kg), (G3) APAP (250 mg/kg)+silymarin (250 mg/kg), (G4) APAP (250 mg/kg)+Vitamin C (200 mg/kg), (G5) APAP (250 mg/kg)+Vitamin C (200 mg/kg)+MD (250 mg/kg), and (G6) APAP (250 mg/kg)+Vitamin C (200 mg/kg)+MD (500 mg/kg). All animals in groups G2-G6 received the respective drug or ally according to their treatment group for 42 days, one hour prior to acetaminophen induction. Results were analysed using one-way ANOVA for statistical significance. Results: The results demonstrated that rats given a therapeutic dose of APAP for 42 days experienced substantial histological alterations alongside elevated blood chemistry indicators. Co-administration of Momordica dioica extract resulted in significantly fewer histopathological lesions and restored or decreased levels of the tested blood chemistry parameters. Rats treated with silymarin exhibited no histological alterations, while liver histology in the Momordica dioica extract group revealed (100%) normal hepatic architecture with minor alterations. According to histochemical staining, APAP-induced hepatotoxicity was characterised by minimal to mild fibrosis (6/6), hydropic degeneration (6/6), necrosis (6/6), and steatosis (6/6). Conclusion: The oral co-administration of Momordica dioica extract possesses significant hepatoprotective properties and mitigates APAP-induced hepatotoxicity by enhancing its antioxidant role and improving tissue integrity. Momordica dioica supplementation could represent an effective treatment against APAP-induced hepatotoxicity.